2013
DOI: 10.1088/0031-9155/58/10/3359
|View full text |Cite
|
Sign up to set email alerts
|

Towards real-time VMAT verification using a prototype, high-speed CMOS active pixel sensor

Abstract: This work investigates the feasibility of using a prototype complementary metal oxide semiconductor active pixel sensor (CMOS APS) for real-time verification of volumetric modulated arc therapy (VMAT) treatment. The prototype CMOS APS used region of interest read out on the chip to allow fast imaging of up to 403.6 frames per second (f/s). The sensor was made larger (5.4 cm × 5.4 cm) using recent advances in photolithographic technique but retains fast imaging speed with the sensor's regional read out. There i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Zin et al investigated the use of a prototype complementary metal oxide semiconductor active pixel sensor (CMOS APS) as a real-time verification tool. The acquisition rate of this device is approximately 21 fps, which was shown to increase the accuracy of the DMLC detection (Zin et al 2013). However, the CMOS APS EPID is still in the prototype stage, and is not used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Zin et al investigated the use of a prototype complementary metal oxide semiconductor active pixel sensor (CMOS APS) as a real-time verification tool. The acquisition rate of this device is approximately 21 fps, which was shown to increase the accuracy of the DMLC detection (Zin et al 2013). However, the CMOS APS EPID is still in the prototype stage, and is not used clinically.…”
Section: Introductionmentioning
confidence: 99%
“…Based on testing of VMAT verification with a highspeed CMOS active pixel sensor (400 Hz), it was found that a synchronization with beam pulses was required for accurate dose rate verification. 33 Furthermore, combined W-FFT filtering was resulting in an additional computation time with respect to a synchronized MV readout. Such an additional delay could be disadvantageous for real-time applications of soft-tissue or marker detection on MV images acquired during treatment.…”
Section: Hzmentioning
confidence: 99%
“…To minimise this further a Monolithic Active Pixel Sensor (MAPS) was used to build a prototype, this was based on the initial work described here [8], which also resulted in intellectual property being generated [9]. The trend in treatments to be more dynamic also motivates MAPS technology, with good S/N and fast frame rates making real-time monitoring and verification a very real possibility [10] [11].…”
Section: Introductionmentioning
confidence: 99%